State anxiety change after a parachute jump and its determinants: gender, experience, and temperament features - Bołdak Agnieszka; Guszkowska Monika (Sciendo, 2014)
Study aim: To determine the role of gender and experience level as factors differentiating state anxiety before and after a parachute jump, and to ascertain relationships between state anxiety and temperament features.